Evaluating a shortened interpretation criterion for intraoperative parathyroid hormone monitoring in patients with primary hyperparathyroidism: 5‐minutes criterion in primary hyperparathyroidism and intraoperative algorithm. Issue 12 (26th November 2018) - Riss, Philipp; Dunkler, Daniela; Selberherr, Andreas; Brammen, Lindsay; Heidtmann, Julian; Scheuba, Christian
Abstract: Background: Most criteria require a parathyroid hormone (PTH) decline of ≥50% within 10 minutes after excision of the gland during surgery for primary hyperparathyroidism. The aim was to evaluate a model allowing earlier prediction of cure. Methods: One thousand eighteen patients with primary hyperparathyroidism were included. A ≥50% decline from baseline within 10 minutes after excision intraoperatively predicted complete removal of hypersecreting tissue. The data were reanalyzed regarding a criterion, requiring a ≥50% decline after 5 minutes. Based on the data and the present literature, an algorithm was created. Results: Assay predicted cure in 854 patients (true‐positive; 83.89%) after 10 minutes (false‐positive [FP] in 13 patients; 1.52%). Nevertheless, only 14 (1.83%) showed persisting disease. According to the "5 minutes" criterion, 723 patients (71.02%) showed a ≥50% decline from baseline within 5 minutes and 10 (1.38%) patients had a FP decline (sensitivity 0.75, specificity 0.86). Conclusion: Using a modified criterion, surgery can be discontinued 5 minutes earlier in 71%.